ANALISIS IMPLEMENTASI PSAK 16 PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - MUFIDA, LULUK (Jurnal Akuntansi AKUNESA, 2019)
This study examines the implementation of PSAK 16. The sample used is a mining company listed on Indonesia Stock Exchange in 2017. The type of data is secondary data sourced from financial statement of the companies. The sampling technique used is purposive sampling and obtained 41 data of mining companies were listed in Indonesian Stock Exchange. Data analysis techniques used are descriptive analysis techniques. The results of the study indicate that mining companies have reported that fixed assets under PSAK 16. More mining companies use the cost model than the revaluation model.Keywords: PSAK 16, Fixed Assets, Cost Model, Revaluation Model